2010
DOI: 10.1080/10790195.2010.10850336
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Strategic Reading with University EFL Learners

Abstract: Collaborative Strategic Reading with University EFL LearnersThe present study was an attempt to probe into the feasibility and effectiveness of a reading instructional approach called MCSR-Modified Collaborative Strategic Reading. Based on a pretest-posttest design, MCSR was implemented with 42 university-level EFL freshmen. They met once a week and received EFL reading instruction according to MCSR for 90 minutes over six weeks. A researcher-developed reading comprehension test was group-administered at prete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 20 publications
3
26
1
Order By: Relevance
“…This is because the way the instructor provided feedback in a positive and encouraging manner did not hinder their interest to learn. This affirms the study by Zoghi et al (2010), Berne and Clark (2006) on group work. In addition, the students in the study were no longer afraid to pose question to the instructor because she provided feedback willingly.…”
Section: Motivation To Readsupporting
confidence: 67%
“…This is because the way the instructor provided feedback in a positive and encouraging manner did not hinder their interest to learn. This affirms the study by Zoghi et al (2010), Berne and Clark (2006) on group work. In addition, the students in the study were no longer afraid to pose question to the instructor because she provided feedback willingly.…”
Section: Motivation To Readsupporting
confidence: 67%
“…Moreover, in reaching a decision on whether to make use of individual or collaborative learning activity, the level of the cognitive capacity of the learner play the key determining factors [22]. The considerable inclination of the students for collaborative learning and learning to indicate the effectiveness of social media support collaborative learning (SSCL) outcomes [23].…”
Section: Related Workmentioning
confidence: 99%
“…In another study with English as a foreign language (EFL) learners, Zoghi, Mustapha, Maasum, and Mohd (2010) found that EFL learners have positive attitudes towards collaborative strategies of reading. Annamma et al, (2011) interviewed 17 middle school teachers.…”
Section: The Effectiveness Of Csrmentioning
confidence: 99%